Supporting young L2 English learners with word recognition: design of early reading materials - Ellis, Melanie (Neofilolog, 2022)
This theoretical article presents a case for a new approach to the teaching of word recognition in English as a foreign language to young learners in Polish early years education, arguing that there is a need for greater attention to explicit instruction in alphabetic principles, selected phonics and decoding skills. Research in first language (L1) English and foreign language (L2) development of word recognition skills is outlined. Differences between the orthographies of Polish and English are highlighted. Approaches used in L1 early reading instruction are contrasted with those commonly applied in L2 settings. The need for more explicit instruction is rationalized on the basis of a brief description of impressions from 20 hours of classroom observation. The second part of the paper presents some principles for the design of materials to introduce alphabetic principles of English and elements of phonics to support word recognition, with examples. The ability to recognize words rapidly and with ease is a key skill, which, unless mastered early, could potentially have a negative impact on the whole of a child’s language education.